Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/ene.12337
|View full text |Cite
|
Sign up to set email alerts
|

Association of candidate genetic variants with restless legs syndrome in end stage renal disease: a multicenter case−control study in Taiwan

Abstract: The genetic variants of primary RLS candidate genes did not play a major role in our uremic RLS populations. The ethnic difference and heterogeneous etiologies underlying renal failure may partly explain the minor genetic contribution to uremic RLS in our populations. Further studies for other ethnicities will be of worth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…ESRD with RLS was associated with an elevated risk of cardiovascular events (OR=2.8, 95% CI 2.0–4.1) compared to ESRD without RLS. RLS severity had a strong influence on this relationship, with OR=1.7 (95% CI 1.0–2.9), 2.8 (95% CI 1.6–4.7) and 2.9 (95% CI 2.0–4.5) for mild, moderate, and severe cases respectively [13]. Similar associations were observed for stroke.…”
Section: Epidemiology Of Restless Legs Syndrome and Cardiovascularmentioning
confidence: 64%
“…ESRD with RLS was associated with an elevated risk of cardiovascular events (OR=2.8, 95% CI 2.0–4.1) compared to ESRD without RLS. RLS severity had a strong influence on this relationship, with OR=1.7 (95% CI 1.0–2.9), 2.8 (95% CI 1.6–4.7) and 2.9 (95% CI 2.0–4.5) for mild, moderate, and severe cases respectively [13]. Similar associations were observed for stroke.…”
Section: Epidemiology Of Restless Legs Syndrome and Cardiovascularmentioning
confidence: 64%
“…There are negative data from association efforts relevant to putative migraine and multiple sclerosis comorbidities with RLS . There was a nominally significant association of PTPRD rs4626664 alleles (odds ratio of 1.5) with symptomatic RLS in a sample of uremic patients, but no significant association of rs1975197 . There was no association with either SNP in another report .…”
Section: Ptprd Genomic Variation and Ptprd Associations With Human DImentioning
confidence: 96%
“… 26 A Taiwanese study of RLS caused by ESRD demonstrated a negative association with the MEIS1 gene. 38 Such inconsistent data might be attributable to differences in genotype or allele frequencies among races. In fact, the rs 6710341 genotyped in our study showed a minor allele frequency which is somewhat different from that in the past study.…”
Section: Discussionmentioning
confidence: 99%